THE EFFECT OF ADVERSITY QUOTIENT ON STUDENTS’ MATHEMATICAL PROBLEM SOLVING ABILITY IN PROBLEM BASED LEARNING MODEL WITH EDMODO - Amidi, W; Dewi, Nuriana Rachmani; Chaniago, Aulia Febliana (International Journal of Psychosocial Rehabilitation, 2020)
The development of education which rapidly increases requires students to have good mathematical problem solving ability. A good mathematical problem solving ability can be enhanced with appropriate learning strategies and a compatible media. The aim of this study was to find out and describe the effect of Adversity Quotient and mathematical problem solving ability in Problem Based Learning (PBL) model learning with Edmodo. This study used true experimental design in the form of posttest-only control design and one class as an experimental class. To analyze the data, this study used simple linear regression test. In brief, this study showed that the impact of Adversity Quotient occurred on students’ mathematical problem solving ability in PBL learning model with Edmodo.